PEMBUATAN DAN UJI KARAKTERISTIK PAPAN SERAT DARI SERAT SABUT KELAPA DAN PLASTIK POLIPROPILENA DAUR ULANG - Syahdilla Fadel Muhammad; Abu Hasan; Fadarina (KINETIKA, 2021)
The use of wood as industrial raw material has increased every year, while the availability of wood has decreased. Besides that, the increase in plastic waste is also a big problem. By making fiberboard from coconut coir fiber and recycled polypropylene plastic, it is hoped that it can increase the added value of coconut coir so that it can become a substitute material to replace the increasingly limited use of wood and also as a way to minimize polypropylene plastic waste in the environment. Based on the test results, the best fiberboard is a fiber board with a random arrangement of fibers with a pressing time of 60 minutes with a moisture content value of 1.18%, a density value of 0.48%, a water absorption value of 4.14%, a thick swelling value. amounted to 4.52%, the MOE value was 4050.80 kg/cm3, and the MOR value was 242 kg/cm3. Overall, the random fiber arrangement fiberboard with a pressing time of 60 minutes has met the SNI 03-2105-2006 standard, but only the MOE value has not met the standar